Visual Merchandising Influence and Display Product on The Decision of Consumer Purchase on Stroberi Store Thamrin Plaza Medan - ain nur harahap (Universitas Harapan Medan, 2020)
ABSTRACT The purpose of this research was to know and analyze the Visual influence of merchandising and display product to the decision of consumer purchase on Stroberi Store Thamrin Plaza Medan. Sample techniques used non probability sampling with Accidental sampling. The samples in this study amounted to 52 respondents. The data sources in this research from primary data are through questionnaires. Test results of F tests showed that the free variable was visual Merchandising (X1) and display product (X2) simultaneously affects the variable (Y) consumer purchase decision on strawberries in the Store Thamrin Plaza Medan and positively influential with significant extent (α) is 5%. With the result of Fobserved (103.562) > F table (3.19), it was concluded that visual merchandising and display product jointly significantly influence the decision of purchasing on Stroberi Store Thamrin Plaza Medan. The value of the coefficient of determination in which the test result of the R figure of 0.899 indicated that the correlation or strong relationship between visual merchandising and display product with a purchase decision of 89.9%. The R Square 0.809 number means variables mean that the free variables (visual merchandising and display product) are able to explain the bound variables (purchase decisions) by 80.9% and the remaining 19.1% of the purchase decision variables are explained by other variables outside of the study. Keywords: Visual Merchandising and Display product, consumer purchase decisions